Perlindungan Hukum Terhadap Pekerja Kilang Migas Dari Risiko Bahan Berbahaya Dan Beracun Berdasarkan Undang Undang No. 1 Tahun 1970 - Dwi Pratiwi Markus; Aristarkus Momot (Jurnal Hukum Lex Generalis, 2026)
The oil and gas refinery industry is a high-risk occupational sector with direct exposure to hazardous materials (B3), which has the potential to cause workplace accidents and long-term occupational diseases. This study aims to analyze the regulation and effectiveness of occupational safety standards based on Law Number 1 of 1970 concerning Occupational Safety for oil and gas refinery workers. A normative legal method with a statutory and conceptual approach was used. The results indicate that occupational safety regulations are still general, not risk-based and do not specifically regulate protection against B3 exposure in the oil and gas industry. Furthermore, weak supervision and low enforcement of sanctions mean that legal protection has not been optimally implemented.